Communication in the Era of Media Convergence and Tourism Enhancement in Samut Songkhram Province Based on the Digital Economy - Srihirun, Wiroj; Pruktara, Tanit; Tungwongchai, Naphat; Thongmak, Sirikarn (Journal of Ecohumanism, 2024)
This qualitative research aims to explore the problems and obstacles of communication in the era of media convergence for tourism promotion and the ability to enhance tourism in Samut Songkhram Province based on the digital economy. An in-depth interview was used to collect data from 27 people: Samut Songkhram representatives or community leaders, tourists, and communication and tourism scholars. The data was analyzed by content analysis and interpretation to present a descriptive narrative. The findings revealed that problems and obstacles to communication in the era of media convergence include the need for a more concise communication process in tourism. Many steps in coordinating cause inconvenience and slowness, which is considered a high cost and expenditure for communication in tourism. As for communication, the era of media convergence and the ability to enhance the provincial tourism of Samut Songkhram based on the digital economy, the respondents thought that they should use integrated communication that combines all platform media to foster innovation in development and support the economy from the grass root which creates and distributes income to residents in Samut Songkhram community. They should develop technological skills and creativity to achieve excellence so the community can adapt to the current and future changes. In this regard, the discussion revealed interesting information that communication in the era of media convergence, where content is delivered across multiple platforms simultaneously, can be used as a guideline to elevate Samut Songkhram tourism with the concept of "Digital Economy Creative Tourism," which Samut Songkhram communities must adjust to keep up with changes that occur all the time.